2013
DOI: 10.1111/epi.12479
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delays in children with early onset epilepsy: Impact, reasons, and opportunities to improve care

Abstract: Purpose Delayed diagnosis of early-onset epilepsy is a potentially important and avoidable complication in epilepsy care. We examined the frequency of diagnostic delays in young children with newly presenting epilepsy, their developmental impact, and reasons for delays. Methods Children who developed epilepsy before their third birthday were identified in a prospective community-based cohort. An interval ≥1 month from second seizure to diagnosis was considered a delay. Testing of development at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 32 publications
(52 reference statements)
4
95
1
2
Order By: Relevance
“…However, in many patients it is unclear if “preexistent” abnormal development was unrelated to, or a first sign of “late recognized” ESES. Diagnostic delay is an important issue in children with epilepsy (especially in syndromes with nonconvulsive seizures or status epilepticus) and is associated with more severe cognitive impairment . In our multivariate analysis the number of previous treatments was not associated with treatment efficacy.…”
Section: Discussioncontrasting
confidence: 90%
“…However, in many patients it is unclear if “preexistent” abnormal development was unrelated to, or a first sign of “late recognized” ESES. Diagnostic delay is an important issue in children with epilepsy (especially in syndromes with nonconvulsive seizures or status epilepticus) and is associated with more severe cognitive impairment . In our multivariate analysis the number of previous treatments was not associated with treatment efficacy.…”
Section: Discussioncontrasting
confidence: 90%
“…Parents perceived these barriers to be most pronounced early in the journey, prior to the referral for presurgical evaluation. Although prior literature has reported parental difficulty with recognition of initial epileptic seizures in children that may result in delays in seeking medical care, 30,31 we found that although the majority of parents did not know that their child was having a seizure that very first time, most parents, nonetheless, sought urgent or emergent medical attention. Furthermore, the time from second AED failure to presurgical referral was ≥1 year in nearly two thirds of children, perhaps highlighting that the interval from two AED failures until access at a pediatric epilepsy center for presurgical evaluation is a critical window for interventions targeting barriers.…”
Section: Discussionmentioning
confidence: 63%
“…Rapid genetic diagnosis is beneficial for appropriate disease management and may improve long-term outcomes in epileptic encephalopathies. 2-4 …”
Section: Discussionmentioning
confidence: 99%